Upper airways abnormalities and tracheal problems in Morquio's disease. Issue 5 (1st May 2003) - Walker, P P; Rose, E; Williams, J G
Abstract : Morquio's disease is a metabolic disorder that can cause various respiratory abnormalities. Patients who live into adulthood are likely to develop upper airway problems and respiratory failure. With advances in home ventilation, these patients are increasingly likely to be referred to specialist respiratory units. We describe our experiences with two such patients.